IMPLEMENTASI PERANGKAT DIGITAL UNTUK MENINGKATKAN KEAKTIFAN SISWA DALAM PEMBELAJARAN: Implementation of Digital Devices to Enhance Student Engagement in Learning - Muhammad Azamuddin Syahapala; Yusrina Nur Amalia Sabila; Afif Alauddin; Sigit Dwi Laksana (STAI Ma'had Aly Al-Hikam Malang, 2025)
Collaboration between education and technology can support the advancement of learning systems. However, the implementation of technology in education still poses many problems. This study analyzes the implementation of digital devices in learning using a qualitative approach and a literature review. Data were obtained using documentation techniques from various literature relevant to the research theme. The results of this study show that the implementation of digital devices accompanied by appropriate learning strategies has been proven to increase student activity in learning. The strategy for developing digital devices in learning requires the participation and leadership of a good principal, the development of human resource competencies, the integration of technology into learning, and external support. The advantages of digital-based learning are: visualization, variety, interactivity, accessibility, creativity, and flexibility. Meanwhile, the disadvantages include: lack of confidence among educators, ignorance among educators, unequal digital access, external disturbances, differences in student learning styles, and cost and digital skills. Kolaborasi antara pendidikan dan teknologi dapat menunjang kemajuan sistem pembelajaran. Namun, implementasi teknologi dalam pendidikan masih menimbulkan banyak permasalahan. Penelitian ini menganalisis implementasi perangkat digital dalam pembelajaran dengan pendekatan kualitatif dan jenis penelitian studi pustaka. Data diperoleh dengan teknik dokumentasi dari berbagai literatur yang relevan dengan tema penelitian. Hasil penelitian ini memaparkan bahwa implementasi perangkat digital yang disertai strategi pembelajaran yang tepat, terbukti meningkatkan keaktifan siswa dalam pembelajaran. Strategi pengembangan perangkat digital dalam pembelajaran membutuhkan peran serta kepemimpinan kepala sekolah yang baik, pengembangan kompetensi SDM, integrasi teknologi ke dalam pembelajaran dan dukungan eksternal. Kelebihan pembelajaran berbasis digital adalah: Visualisasi, Varifatif, Interaktif, Aksesibilitas, Kreativitas dan Fleksibilitas. Sedangkan kelemahannya antara lain: Kurangnya kepercayaan diri pendidik, Ketidaktahuan pendidik, Ketidaksetaraan akses digital, Gangguan eksternal, Perbedaan gaya belajar siswa serta Biaya dan keterampilan digital. Kata Kunci : Digitalisasi Pendidikan; Perangkat Digital; Siswa Aktif; Strategi Pembelajaran.